(untitled) (Research, Society and Development, 2023)
This article brings the results of a bibliographical survey of articles published in teaching Chemistry, specifically those dedicated to Quantum Chemistry. The methodology used was of a qualitative nature, looking for the identification and collection of publications on this subject in the Web of Science database, using the search expression “quantum chemistry” and “teaching”. As a result, a total of 13 articles were obtained. From the analytical process, it was concluded that there is a gap in the teaching of Quantum Chemistry in Basic Education since the accessed publications bring results about research carried out in Higher Education and Post-Graduation, as well as free courses, to the detriment of those directed to Basic Education. Another observation of the analysis is that of the 13 articles, 11 used computational technologies, applications, simulators, or something similar to improve teaching and learning.